The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnhum.2021.729051
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptors: A Key Piece in the Puzzle of Memory Retrieval

Abstract: Retrieval constitutes a highly regulated and dynamic phase in memory processing. Its rapid temporal scales require a coordinated molecular chain of events at the synaptic level that support transient memory trace reactivation. AMPA receptors (AMPAR) drive the majority of excitatory transmission in the brain and its dynamic features match the singular fast timescales of memory retrieval. Here we provide a review on AMPAR contribution to memory retrieval regarding its dynamic movements along the synaptic compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 144 publications
1
5
0
Order By: Relevance
“…Our data showed that the e E/I ratio in the hippocampus was not different in MCI or AD; however, lower amplitudes of GABA A Rs and AMPARs currents in the hippocampus were associated with lower cognitive scores, indicating that hippocampal atrophy, with total loss of excitatory and inhibitory synapses, correlates better with cognitive impairment, as observed in hippocampal sclerosis studies [ 80 ]. This is also in agreement with strong evidence supporting the relationship between positive modulation of hippocampal AMPARs [ 50 , 56 , 68 , 93 ] with better cognition. In contrast, we found that a gain of function of AMPARs in parallel with GABAergic deficits lead to a striking pro-excitatory shift of the E/I balance in the TCx of AD individuals across various levels of analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Our data showed that the e E/I ratio in the hippocampus was not different in MCI or AD; however, lower amplitudes of GABA A Rs and AMPARs currents in the hippocampus were associated with lower cognitive scores, indicating that hippocampal atrophy, with total loss of excitatory and inhibitory synapses, correlates better with cognitive impairment, as observed in hippocampal sclerosis studies [ 80 ]. This is also in agreement with strong evidence supporting the relationship between positive modulation of hippocampal AMPARs [ 50 , 56 , 68 , 93 ] with better cognition. In contrast, we found that a gain of function of AMPARs in parallel with GABAergic deficits lead to a striking pro-excitatory shift of the E/I balance in the TCx of AD individuals across various levels of analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Hippocampal synaptic fractions were analyzed for expression of to investigate sex differences in molecular mechanisms underlying VOMA induced working memory deficits. GluA1 and GluA2 are markers known to be involved in synaptic plasticity for short-term and long-term memory respectively [ 40 , 41 ]. A two-way repeated measures ANOVA of hippocampal GluA1 expression [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the AMPAR signaling pathways that drive synaptic plasticity have not been fully investigated in MA-induced memory deficits. GluA1 and GluA2 are AMPARs known to be involved in synaptic plasticity processes with direct implications in learning and memory [ 40 , 41 ]. AMPAR trafficking is modulated by PKM ζ to sustain LTP processes [ 42 , 43 ] and conversly by glycogen synthase kinase 3 β (GSK3 β ) to promote LTD [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, encoding can trigger a cascade of signal induction and transduction [ 50 ]. For initial induction, findings have consistently suggested the importance of glutamatergic receptors, such as NMDA and AMPA receptors in forming short- and long-term memory [ 51 , 52 ]. However, partially dissociative molecular mechanisms for short-term and long-term memory have been reported.…”
Section: Discussionmentioning
confidence: 99%